2011
DOI: 10.1002/cne.22620
|View full text |Cite
|
Sign up to set email alerts
|

Identification of urocortin 3 afferent projection to the ventromedial nucleus of the hypothalamus in rat brain

Abstract: Urocortin 3 (Ucn 3) is a corticotrophin-releasing factor related neuropeptide with potent anorectic effects in the brain. Ucn 3 nerve fibers heavily innervate the hypothalamic ventromedial nucleus (VMH) and injection of Ucn 3 into the VMH suppresses feeding. Currently, the origin of the Ucn 3 afferent input into the VMH is unknown. In the present study, anatomical tracing shows the major Ucn 3 afferent input to the VMH resides in the anterior parvicellular part of the paraventricular nucleus of the hypothalamu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 55 publications
5
36
0
Order By: Relevance
“…The VMH, which is densely innervated by Ucn3-positive fibers [8,37], expresses CRF 2 receptor mRNA [5]. The CRF 2 receptor-expressing glutamatergic neurons of the VMH project to the ARC, and stimulate production of an anorectic neuropeptide, proopiomelanocortin [10].…”
Section: Discussionmentioning
confidence: 99%
“…The VMH, which is densely innervated by Ucn3-positive fibers [8,37], expresses CRF 2 receptor mRNA [5]. The CRF 2 receptor-expressing glutamatergic neurons of the VMH project to the ARC, and stimulate production of an anorectic neuropeptide, proopiomelanocortin [10].…”
Section: Discussionmentioning
confidence: 99%
“…Using optogenetic and in vivo recording methods, a distinct region within the HAA, the ventrolateral subdivision of the ventromedial hypothalamic nucleus (VMHvl), was recently shown to be necessary and sufficient for offensive aggression in mice (Lin et al, 2011). Afferents to the VMH are also numerous, and include other hypothalamic nuclei, the bed nucleus of stria terminalis , lateral septum, and amygdala (Berk and Finkelstein, 1981; Chen et al, 2011; Luiten and Room, 1980). The substantial connections of the VMH suggest that there are multiple nodes of neuromodulatory control over agonistic behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous anatomical study showed that the main source of Ucn 3 input into the VMH originates in the PVHap and the adjacent BSTp. The MEA provides moderate Ucn 3 afferent projections (Chen et al, 2011). Ucn 3 cells in the median preoptic nucleus supply negligible input into the nucleus (Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The MEA provides moderate Ucn 3 afferent projections (Chen et al, 2011). Ucn 3 cells in the median preoptic nucleus supply negligible input into the nucleus (Chen et al, 2011). Interestingly, Ucn 3 neurons in the rostral perifornical hypothalamus just caudal and lateral to the PVHap area do not project to the VMH; these cells instead send projections to the LS (Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%